2014
DOI: 10.1071/an13250
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and endocrine profiles of primiparous beef cows grazing native grassland. 1. Relationships between body condition score at calving and metabolic profiles during the transition period

Abstract: The body condition score (BCS) at calving has been postulated as the main factor in the interaction of nutrition and reproduction in beef-cow ecosystems. The objective of the present study was to analyse the effect of BCS at calving on endocrine and metabolic profiles during the transition period in primiparous Hereford cows (n = 56) grazing native grassland. Cow BCS was registered and plasma insulin, insulin-like growth factor-I (IGF-I) and metabolites (concentrations of urea, albumin, cholesterol, total prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Cows, in these conditions, show a negative energy balance and lose BCS (Soca et al, 2014a). As reported in other countries (Houghton et al, 1990;Perry et al, 1991;Stalker et al, 2006), and in our conditions (Quintans et al, 2010;Scarsi, 2012), in the present work, the loss of BCS was greater during prepartum than early postpartum.…”
Section: Discussionsupporting
confidence: 73%
“…Cows, in these conditions, show a negative energy balance and lose BCS (Soca et al, 2014a). As reported in other countries (Houghton et al, 1990;Perry et al, 1991;Stalker et al, 2006), and in our conditions (Quintans et al, 2010;Scarsi, 2012), in the present work, the loss of BCS was greater during prepartum than early postpartum.…”
Section: Discussionsupporting
confidence: 73%
“…However, SUP cows conceived earlier and tended to have greater pregnancy rate than CON cows. In our pastoral conditions, it has been reported that a small difference in BCS at calving (0.6 u) was associated with important differences in metabolic changes (Soca et al 2014a(Soca et al , 2014b. In fact, these authors observed that cows with a BCS of only 0.6 u greater than cows in low BCS (4.1 vs 3.5 for moderate and low BCS cows, respectively), presented higher insulin-like growth factor-1 and early pregnancy rate.…”
Section: Discussionmentioning
confidence: 73%
“…; Soca et al. ). Milk production during early lactation with its associated high nutritional requirements induce a physiological state of negative energy balance (NEB) in most cows (Walsh et al.…”
Section: Introductionmentioning
confidence: 96%
“…Nutrient intake and body energy reserves are major regulators of ovarian function in cattle (Montiel and Ahuja 2005;Roche et al 2007); thus, the loss of body condition score (BCS) at calving and during the postpartum period has been associated with delays in resumption of ovarian cycles (Shrestha et al 2005;Soca et al 2014). Milk production during early lactation with its associated high nutritional requirements induce a physiological state of negative energy balance (NEB) in most cows (Walsh et al 2011;Esposito et al 2014) and delays ovulation in association with a suppression of the frequency of release of luteinizing hormone (LH) from the anterior pituitary gland (Diskin et al 2003;Butler 2005).…”
Section: Introductionmentioning
confidence: 99%